Molecular Analysis of Tumor-Promoting CD8(+) T Cells in Two-Stage Cutaneous Chemical Carcinogenesis - Kwong, Bernice Y. (2009)
T-pro are tumor-infiltrating TCRαβ(+)CD8(+) cells of reduced cytotoxic potential that promote experimental two-stage chemical cutaneous carcinogenesis. Toward understanding their mechanism of action, this study uses whole-genome expression analysis to compare T-pro with systemic CD8(+) T cells from multiple groups of tumor-bearing mice. T-pro show an overt T helper 17–like profile (high retinoic acid–related orphan receptor-(ROR)γt, IL-17A, IL-17F; low T-bet and eomesodermin), regulatory potential (high FoxP3, IL-10, Tim-3), and transcripts encoding epithelial growth factors (amphiregulin, Gro-1, Gro-2). Tricolor flow cytometry subsequently confirmed the presence of TCRβ(+) CD8(+) IL-17(+) T cells among tumor-infiltrating lymphocytes (TILs). Moreover, a time-course analysis of independent TIL isolates from papillomas versus carcinomas exposed a clear association of the “T-pro phenotype” with malignant progression. This molecular characterization of T-pro builds a foundation for elucidating the contributions of inflammation to cutaneous carcinogenesis, and may provide useful biomarkers for cancer immunotherapy in which the widely advocated use of tumor-specific CD8(+) cytolytic T cells should perhaps accommodate the cells’ potential corruption toward the T-pro phenotype. The data are also likely germane to psoriasis, in which the epidermis may be infiltrated by CD8(+) IL-17-producing T cells.